Commentary: It's All About the Quality of Advice, Guidance, and Research for Rural Educators: A Rejoinder to Howley, Theobald, and Howley - Louis F. Cicchinelli; Ceri B. Dean (Journal of Research in Rural Education, 2005)
Howley, Theobald, and Howley (2005) appear to focus on two major issues in their reply to the McREL review (Arnold, Newman, Gaddy, & Dean, 2005): (a) the utility of quantitative study of schools in the "rural lifeworld," and (b) the motivation of McREL staff members for reviewing the content and methods of existing rural education research.